2016
DOI: 10.1371/journal.pone.0154970
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hospital Admissions with Influenza during the 2013/2014 Northern Hemisphere Influenza Season: Results from the Global Influenza Hospital Surveillance Network

Abstract: BackgroundThe Global Influenza Hospital Surveillance Network was established in 2012 to obtain valid epidemiologic data on hospital admissions with influenza-like illness. Here we describe the epidemiology of admissions with influenza within the Northern Hemisphere sites during the 2013/2014 influenza season, identify risk factors for severe outcomes and complications, and assess the impact of different influenza viruses on clinically relevant outcomes in at-risk populations.MethodsEligible consecutive admissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 38 publications
5
42
0
1
Order By: Relevance
“…Concerning the frequency of complications and underlying conditions (Table ), we also found very few significant differences between the influenza viruses in the unadjusted virus comparisons. There was some evidence that A(H1N1)p may result in more complications compared to other influenza virus (sub)types: People infected with A(H1N1)p more often had pneumonia and were more frequently admitted in the ICU compared to influenza B, and more frequently had upper respiratory tract infections, pneumonia, and ICU admissions compared to A(H3N2).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Concerning the frequency of complications and underlying conditions (Table ), we also found very few significant differences between the influenza viruses in the unadjusted virus comparisons. There was some evidence that A(H1N1)p may result in more complications compared to other influenza virus (sub)types: People infected with A(H1N1)p more often had pneumonia and were more frequently admitted in the ICU compared to influenza B, and more frequently had upper respiratory tract infections, pneumonia, and ICU admissions compared to A(H3N2).…”
Section: Resultsmentioning
confidence: 66%
“…An overview of the studies (Table and Table ) showed a lot of diversity in the populations that were investigated: Studies are presented in terms of hospitalized patients (n = 22) or cover mainly outpatient settings (n = 19), such as primary care (n = 6) or community‐based (n = 4) settings. Most studies were carried out in Asia (n = 17), Europe (n = 15), or North America (n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…Results have been published from the network’s first two seasons, 2012–2013 [5, 8] and 2013–2014 [9]. In this report, we describe the influenza epidemiology and vaccine effectiveness results from the GIHSN during the 2014–2015 influenza season.…”
Section: Introductionmentioning
confidence: 99%
“…2 Influenza vaccination is associated with a lower risk of confirmed influenza with an adjusted odds ratio of 0.61. 3 The World Health Organization defined the primary groups for vaccination in 2012. They determined the primary target groups as pregnant women and the secondary target groups as children (6-59 months), older adults, individuals having chronic medical conditions, and health care personnel.…”
mentioning
confidence: 99%